Model Perencanaan Program Humas Sekolah Dasar Berbasis Partisipasi Di SDN Pasar Lama 1 Banjarmasin - Hernawati Hernawati; Nur Sabila Hanifa; Nur Khaliza; Ainal Fitri Khairunnisa; Noor Azizah; Hikmah Hikmah; Suhaimi Suhaimi (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Public relations management in primary schools is very important to strengthen communi-cation and collaboration between schools and the surrounding community. However, in practice, many schools still implement public relations programme planning in an adminis-trative and hierarchical manner, resulting in limited participation from parents and the community. This study aims to analyse a participatory-based public relations programme planning model for primary schools. This study uses a qualitative approach with descriptive research to understand the process of public relations programme planning in schools. The results show that public relations programme planning at SDN Pasar Lama 1 involves the principal, teachers, students, parents, and the community in various school activities. This participation is evident in environmental activities, character building, and community co-operation in maintaining school cleanliness, planting trees, and promoting healthy living. This participatory approach strengthens communication between the school and the com-munity, increases public trust, and supports the success of educational programmes in pri-mary schools.